Pathogenetic Mechanisms of Organ Dysfunction in Severe Concomitant Trauma - G. V. Bulava (Неотложная медицинская помощь, 2023)
Severe concomitant trauma has been a major demographic and medical problem for many years, being the cause of high mortality of the able-bodied population. The simultaneous formation of an array of destroyed tissues triggers a systemic inflammatory reaction, which, against the background of traumatic and hemorrhagic shock, leads to an imbalance in immune reactivity and predisposes to the development of septic complications. The review presents the basic concepts of post-traumatic reactions and violations of the balance of cellular and humoral immune mechanisms leading to the development of complications.